On the evaluation of two-dimensional correlation sequences - Zou Mou-Yan; Unbehauen, R. (IEEE transactions on acoustics, speech, and signal processing, 1987)
An approach to the evaluation of two-dimensional (2-D) correlation sequences and complex integrals is discussed. It is demonstrated that the system of rational function equations given by Hwang can be solved by making use of the unit circle polynomial interpolation. Thus, a general computer algorithm becomes available for handling the problem.